Altering Chain Flexibility of Aliphatic Polyesters for Yellow‐Green Clusteroluminescence in 38 % Quantum Yield. Issue 6 (16th December 2021) - Chu, Bo; Zhang, Haoke; Hu, Lanfang; Liu, Bin; Zhang, Chengjian; Zhang, Xinghong; Tang, Ben Zhong
Abstract: Preparation of non‐conjugated polymers with long‐wavelength emission and high quantum yield (QY) is still a huge challenge. Herein, we report the first example of linear non‐conjugated polyester exhibiting yellow–green clusteroluminescence (CL) and a high QY of 38 %. We discovered that the polyester P3 with balanced flexibility and rigidity showed the longest CL wavelength and highest QY. Systematically photophysical characterization unravel the key role of ester cluster in the CL and the cluster formation via the aggregate of ester units was visualized. Moreover, P3 was demonstrated to be a highly selective, quick‐responsive (ca. 1.2 min) and sensitive detector (detection limit is 0.78 μM) for irons owing to the fast disassociation of clusters by irons. This work not only gains further mechanistic insight into CL but also provides a new strategy to design high‐efficiency and long‐wavelength CL, meanwhile, enlightens the glorious application prospect of luminescent polyester. Abstract : This work reports the novel example of linear non‐conjugated polyester exhibiting yellow‐green clusteroluminescence and a high quantum yield of 38 %. The formation of ester‐unit cluster is responsible for the emission and is decided by balancing flexible and rigid structures of chains.